Integrasi Etnomatematika Dan Model Pembelajaran Inovatif Dalam Pemahaman Luas Layang-Layang Disekolah Dasar: Studi Wawancara Dan Telaah Literatur - Prasya Aliyani; Della Nurkhalifah (JPT : Jurnal Pendidikan Tematik, 2025)
This article aims to describe the kite area learning strategy for elementary school students through an analysis of teacher interviews at SDN 21 Bengkulu Selatan and integrating it with theoretical studies from Neza Agusdianita's journal and supporting ethnomathematics journals. The research data was obtained through structured interviews with elementary school teachers and analyzed descriptively. The results showed that students had difficulty understanding the concept of diagonals, tended to memorize formulas, and lacked concrete experiences. The analyzed literature indicates that ethnomathematics, Realistic Mathematics Education (RME), Project-Based Learning (PjBL), and differentiated learning can be effective solutions in fostering students' conceptual understanding. This article emphasizes that contextual, culture-based mathematics learning and utilizing concrete media can improve students' mathematical literacy and understanding of geometry.